Evaluation of correlation between compliance of a patient towards orthodontic treatment and plaque accumulation in lower anterior region with fixed orthodontic appliances. A cross-sectional study - Hafsa Riaz; Maria Tanveer (Journal of University Medical & Dental College, 2024)
BACKGROUND &OBJECTIVE: Using orthodontic appliances can offer new spots for the oral microbiota and dental plaque to attach. Poor oral hygiene can lead to gingivitis and tooth decay resulting in the removal of braces to repair damage and delay treatment. Orthodontic patients who are mindful of their oral health often show greater compliance with their treatment. They tend to miss fewer appointments and avoid losing brackets, demonstrating a strong commitment to their orthodontic care. This study aims to find a correlation between plaque accumulation and patients’ compliance with their orthodontic treatment. METHODOLOGY:50 orthodontic patients (20 males and 30 females, aged 11 to 25 years) were assessed at their 3rd, 4th, or 5th appointments. The plaque index for each patient was calculated on these appointments. Patient compliance like appointment follow-ups and bracket failures was recorded. A correlation was found between the plaque index and compliance of the patient. RESULTS: A statistical analysis revealed a significant, strong negative correlation between the rate of following appointment follow-ups and the plaque scoring index (r = -0.832, P value < 0.001), and a significant, strongly positive correlation between bracket failure rate and plaque scoring index (r = 0.795, P < 0.001). Patients who had good attendance at follow-up appointments and low bracket failure had lower mean plaque score indices. CONCLUSION: Patients with good compliance in terms of low bracket failure rate and attending follow-up appointments regularly tend to have lower plaque scores.